The Impact of Deconstruction on the Lithuanian Literary Criticism - Jurgutienė, Aušra (Literatūra, 2021)
In the article I discuss how deconstruction (Jacques Derrida and other Yale School participants) came to Lithuanian literary criticism and how it changed habits of humanitarian thinking during the three decades after independence. The most unusual and radical deconstruction critique of essentialist metaphysical thinking, new terminology (inter-text, elimination of center, footprint, writing, difference, blinding, labyrinth narrative, guest / enemy, etc.) and new strategies for interpreting texts were very important for Lithuanian humanities liberated from Soviet ideology. Literary critics have noticed and discussed the undoubted connection between postmodernist literature and its deconstructive reading. We can find three tendencies in the deconstructive criticism of Lithuanian literature. The first tendency is the interpretation of general theoretical concepts of deconstruction, second tendency - searching the deconstructive features in literary works and the third tendency of criticism, expanding its own self-criticism and self-irony, is discussing chrestomathic and structuralist interpretations of the literary works or deconstructing icons of Soviet culture. We know very well, that many feminist, postcolonial, historiographic, anthropological, or interdisciplinary researches of literature cannot escape the effects of deconstruction.